If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + -5 = 15 Reorder the terms: -5 + 6a = 15 Solving -5 + 6a = 15 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 6a = 15 + 5 Combine like terms: -5 + 5 = 0 0 + 6a = 15 + 5 6a = 15 + 5 Combine like terms: 15 + 5 = 20 6a = 20 Divide each side by '6'. a = 3.333333333 Simplifying a = 3.333333333
| 39+1=1+11 | | 2(x-6)(x-6)+18=56 | | -3-4x=29 | | -30x+2=20+15x | | x-70=10(2x+3)-24 | | 18=3w | | x-10x=8 | | 9/3=-39 | | 50=-5(2w+4) | | 5x+5x^2=20 | | 8p+5=2p+13 | | 5p-15=-6 | | -7(x+6)+48=10-8x | | 4x^3-13x^2-5x+2=0 | | 3b-2=b-2 | | 660=x(6)+y(3)+25 | | 16-3(5-3x)=6x+2 | | 81=9(5a-1) | | 16-3(5-3x)=6x+3 | | x^3+2x^2=60 | | -t^2+3t-2=0 | | -5(v+4)=-35 | | (v^3/-2u)^3 | | 2x+3y=-30 | | -(11d-v)= | | 6(x-5)=-9(5+x) | | (−27x^3)^(4/3) | | 7(x-1)=-21 | | 5x+2(c+6)= | | 2ax^2-4ax+a+1=0 | | (9+x)4=2(19-5) | | -2+3x=-6+25 |